(untitled) (Applied Biological Research, 2024)
The insect gut is a complex system colonized by a consortium of microbes whichshare a symbiotic relation with the host and also contribute to its growth, development, immunity and defense against its enemies, reproduction and speciation, thereby play a crucial role in its survival. Hence understanding the role of these bacteria is a crucial step for using them in microbial control of pests. In present study, a 16S microbiome profiling of gut of Epilachna vigintioctopunctata was carried out. The study revealed 553 operational taxonomic units (OTUs). The majority of bacterial OTUs belonged to the phylum Proteobacteria, followed by Bacteroidetes, Firmicutes and Actinobacteria. The majority of bacterial OTUs belonged to the family Halomonadaceae which was the most abundant taxa in larval gut. The study provides a baseline information on gut inhabiting microbes of E. vigintiocto punctata up to the genus level for most phyla.